UPAYA PENINGKATAN BERAT BADAN BALITA KURANG DENGAN PEMBERIAN MAKANAN TAMBAHAN DI DESA KEDUNGPANJI MAGETAN - Cintika Yorinda Sebtalesy; Sesaria Betty Mulyati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
Abstract: The toddler period is the first five years of every human child's life. During the golden age of malnutrition in toddlers, at this time 90% of a child's brain cells grow and develop. Development and growth as a success factor for growth and development in the future Underweight needs to be watched out for, because the impact is underweight under the red line (BGM). In Kedungpanji Village there are 16 toddlers with underweight. Factors causing malnutrition under five are determined by 3 things, namely the child does not get enough balanced nutritious food, the child does not receive adequate nutritional care and the child may suffer from infectious diseases. As for minimizing underweight, namely improving nutrition with PMT Banana Date-Based Innovation Smoothies Recovery which aims to improve the nutritional quality of individuals and communities. For this reason, it is necessary to provide additional food in Kedungpanji Magetan Village. The results of this activity were that before being given PMT smoothies based on banana dates the average body weight decreased by 83.3% after being given smoothies the weight increased to 88.9%.